PSYCHOLOGICAL AND PHYSIOLOGICAL FACTORS THAT ENSURE THE CHILD'S COMMUNICATIVE ACTIVITY IN THE PROCESS OF SPEECH FORMATION - Maxmudova Madinaxon Sobirxonovna; Rahmatova Dilnavozxon Izzatilla qizi (Bright Mind Publishing, 2025)
The article reflects the psychophysiological foundations of human speech activity, the psychological foundations of oral speech and the scientific opinions of scientists on this matter, the ideas about the acquisition of paradigmatic and syntagmatic relations of the grammatical system of speech.
Keywords: Speech development, psychophysiological basis of speech, speech mechanism, grammatical aspect of speech, lexical process, language features.